Peningkatan Efisiensi Sistem Pencahayaan Dan Pendingin Gedung Bertingkat Berbasis Green Building - Eko Suryo Sunarwanto (Sekolah Tinggi Teknik - PLN, 2020)
Waste of energy in a building causes increase in operating costs for electricity bills. To solve this problem, a building requires energy management planning. Energy Consumption Intensity (IKE) is used to know the energy requirements usage in buildings. Redesign the lighting and cooling system used a simulation model of room lighting and heat loads using the Dialux simulation software for lighting and DACCS for cooling. The results of energy simulation calculations using the Dialux and DACCS software,lighting that uses energy-efficient lamps and utilizes daylight, with inverter cooling with high coefficient of performance is proven to save energy operating costs of 6,904.32 kWh / month and 82,851.84 kWh / year. The results of the Life Cycle Cost that have been carried out show that the use of the existing system for 5 years costs Rp. 3,014,021,105. By using the redesign system costs Rp. 2,937,693,255. The redesign system can save as much as Rp. 76,327,850.